A Simple, Accurate and Highly Secure Method to Encrypt-Decrypt Digital Images - Jamil Azzeh; Ziad Alqadi; Qazem Jaber (Society of Visual Informatics, 2020)
The digital image may be important and has a secret character, which requires not understanding it when looking at the naked eye or not understanding the contents. So seeking a method of digital image encryption-decryption is a very important task. In this paper we will introduce a new method of digital image encryption-decryption, which will be very simple, highly secure and accurate and highly efficient